Differentiation Strategy Analysis Of Chicken Noodle Bakso Joglo And Its Impact On Customer Satisfaction In Rantauprapat City - Zebua, Yuniman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The purpose of this study was to analyze the differentiation strategy of chicken noodle Bakso Joglo and its impact on customer satisfaction in Rantauprapat City. The approach to this study is descriptive qualitative research. As informants are the owner/leader and several employees of Chicken Noodle Bakso Joglo. Data collection uses interview techniques or structured interviews directly. The population in this study were customers of chicken noodle meatball Bakso Joglo. Samples taken randomly as many as 100 customers. Data analysis techniques use descriptive analysis models with the help of Smart PLS. The results of the study show that: product innovation has a significant effect on customer satisfaction, customer experience has a significant effect on customer satisfaction and service has a positive and significant effect on customer satisfaction